37.7k views
4 votes
What is the result of substituting for yin the bottom equation? y=x+3 y= x^2 + 2x - 4​

User AbelSurace
by
6.1k points

1 Answer

5 votes

Answer:

x +3 = x^2 +2x -4

Explanation:

Straight substitution of the top expression for y gives you ...

x +3 = x^2 +2x -4

__

This lets you rewrite the equation to standard form as ...

x^2 +x -7 = 0

and find the solutions to be ...

x = (-1±√29)/2

Corresponding y-values will be 3 more than this:

y = (5±√29)/2

User MWiesner
by
5.7k points